(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
It is difficult for autopsy surgeon to determine identity and cause of death when deceased was found completely charred due to burning. Meticulous post mortem examination followed by preservation of materials for laboratory investigation will be of crucial importance for law enforcement agency along with proper investigation. We are reporting a case in which charred dead body was brought as unknown person found in driving seat of burnt car and initial investigation indicated that car owner was deceased person (His finger ring was found near body and car number plate visible). During postmortem we found findings suggestive of postmortem nature of burn and reports of preserved materials also consistent with post mortem burns. During postmortem, metallic distorted material also found along with dead body appeared to be bone implant but alleged deceased have not undergone any orthopedic operation and car number plate found without any burning effect in completely burnt car. So both identity and cause of death after postmortem examination found not consistent with facts of initial investigation. Subsequently car owner surrendered and narrated story of killing his friend with planning to simulate his death for insurance claims.